Meningovascular neurosyphilis with basilar artery thrombosis in HIV patient - Edgar Perez Barragán; Elena Urdez Hernández; Bernardo Pérez Orozco; Mariela Sánchez González (Elsevier, 2018)
Currently, neurosyphilis is an uncommon disease and may occur at any stage of syphilis. Co-infection of syphilis with HIV can affect the clinical course. We report a case of meningovascular neurosyphilis in a patient with HIV in whom basilar artery thrombosis and reactive VDRL in CSF were detected. Treatment with penicillin was instituted with adequate response showing clinical improvement. Neurosyphilis is a differential diagnosis in young patients with cerebral infarction, especially in HIV patients. Keywords: Neurosyphilis, Syphilis, HIV